Basal Ganglia Germinoma in an Adolescent: A Case Report - Kulkarni, Shilpa; Ainapure, Anish; Gala, Foram; Shah, Payal; Gavali, Vrushabh (Journal of Pediatric Neurology, 2022)
Germ cell tumors are rare tumors and may pose a diagnostic dilemma. We present a 15-year-old boy with insidious onset right hemiparesis followed by polyuria and polydipsia. Later, he also developed cognitive decline and speech disturbances. Serial magnetic resonance images (MRIs) over a 2-year period showed progressive atrophy of the left caudate nucleus, along with Wallerian degeneration of the left internal capsule and crus of midbrain. Further in the course, imaging revealed an ill-defined signal intensity involving left ganglio-capsulo-thalamic region with increased perfusion which was suggestive of basal ganglia germinoma. Beta human chorionic gonadotropin levels were mildly elevated. This case illustrates an uncommon presentation of a central nervous system germinoma which is often misdiagnosed in the early stages because of its atypical symptomatology and MRI findings.
Keywords: basal ganglia germinoma; adolescent; progressive hemiparesis; ganglio-capsulo-thalamic signal on MRI; mildly elevated β-HCG